العقوبات التعزيرية لترك الالتزام الزكوي وضوابطها في الفقه الإسلامي: (Discretionary Penalties for Neglecting Religious Obligations and Their Regulations in Islamic Jurisprudence) - (Mohammad Kalid Mansour), محمد خالد منصور; (Heba Mohammad Mansour), هبة محمد خالد منصور (At-Tajdid - Intellectual Refereed Journal, 2025)
Research into issues related to the legal rulings of zakāh constitutes one of the most significant areas of contemporary scholarly inquiry. The problem addressed in this study arises from the need to clarify the discretionary punishments (taʿzīr) for failing to fulfil zakāh obligations, as well as the legal parameters governing such punishments in Islamic jurisprudence. The aim of the research was to derive possible punitive measures that may be imposed on those who neglect their zakāh obligations. The study adopted the inductive, analytical, and deductive methodologies. It was structured into an introduction and two main sections.The research arrived at a number of findings, the most notable of which include: that taʿzīr may begin with a preliminary advisory warning to the person liable for zakāh, followed by a final warning, a formal threat, and, if necessary, the forcible seizure of the zakāh funds by the authority. It also includes the possibility of detaining those who withhold zakāh for an appropriate period until the due amount is paid, as well as denying such individuals any preferential benefits offered by the state—such as priority access to government tenders, discounts, or grants. Keywords: Zakāh, taʿzīr, punishments.